Awareness and opinions of Maryland citizens toward Chesapeake Bay Mute Swans Cygnus olor and management alternatives - Hindman, Larry J.; Tjaden, Robert L. (Wildfowl, 2014)
Concerns surrounding the ecological impacts from increasing numbers of non-native Mute Swans Cygnus olor have led some management agencies in the United States to implement control efforts directed at reducing populations of this invasive species. By 2001, concerns regarding the rapid increase in Mute Swan numbers in Maryland (USA) and their negative impacts upon Chesapeake Bay living resources (e.g. submerged aquatic vegetation, native waterfowl and colonial waterbirds) had become acute. An understanding of citizens’ attitudes toward Mute Swans and potential management alternatives is necessary before wildlife agencies can enact socially acceptable measures to control these populations. A random telephone survey of Maryland registered voters therefore was conducted in February 2005 to assess public awareness (knowledge and attitudes) of Mute Swans in Chesapeake Bay, including the size of the swan population, preferences for swan management options and confidence in the ability of the Maryland Department of Natural Resources (MDNR) to control their numbers. A total of 625 completed surveys were obtained from respondents in seven geographical regions. Nearly all respondents (86%, n = 539) indicated they would support Mute Swan population control after they were provided evidence that this species was harmful to the Chesapeake Bay ecosystem; they felt the health of Chesapeake Bay was more important than sustaining a non-native swan population. Of the respondents that supported aggressive control measures, 62% (n = 387) supported the use of lethal methods of control, and a majority supported hunting over egg addling as a control method. Most respondents were also confident that the MDNR would implement control methods that were both humane and effective in solving the overabundance of Mute Swans in the region. The results provide useful information to wildlife professionals for management planning and communication when considering control of Mute Swan populations.